The transport of low-frequency turbulence in the super-Alfvénic solar wind. (September 2015) - Adhikari, L; Zank, G P; Bruno, R; Telloni, D; Hunana, P; Dosch, A; Marino, R; Hu, Q
Abstract: Understanding the transport of low-frequency turbulence in an expanding magnetized flow is very important in analyzing numerous problems in space physics and astrophysics. Zank et al 2012 developed six general coupled turbulence transport equations, including the Alfvén velocity to describe the transport of low-frequency turbulence for any inhomogeneous flows, including sub-Alfvénic coronal flows, and super-Alfvénic solar wind flows. Here, we solve the 1D steady state six coupled turbulence transport equations of Zank et al 2012, and the transport equation corresponding to the solar wind temperature in the super-Alfvénic solar wind flows from 0.29 to 100 AU without the Alfvén velocity. We calculate turbulent quantities corresponding to Voyager 2 data sets for three cases; i) a positive and negative sign of Br ; ii) the azimuthal angle ϕ = tan -1 ( Bt /Br ), and iii) a positive and negative sign of Bt, where Br and Bt are the radial and transverse components of the interplanetary magnetic field, respectively. We compare our theoretical results to the observational results, and find good agreement between them.